Environmental Problems Associated with Methane Production and Strategies to Reduce Methane Emissions from Farm Animals - Fazel, Yaser (Journal of Natural Sciences – Kabul University, 2021)
The increasing release of greenhouse gases into the atmosphere has compelled humanity to develop strategies and policies to mitigate their emissions. Methane, a significant greenhouse gas, is emitted from various sources, including ruminant animals through a digestive process known as enteric fermentation. This study outlines strategies to reduce methane emissions in livestock practices. Most of the proposed strategies focus on manipulating animal feed and optimizing ruminal fermentation. Methods such as incorporating fats and fumaric acid into animal diets, substituting structural carbohydrates with non-structural ones, and using additives like tannins and saponins have shown promise in reducing methane emissions from ruminants.